Plasma cytokines in patients with COVID-19 during acute phase of the disease and following complete recovery - N. A. Arsentieva; N. E. Liubimova; O. K. Batsunov; Z. R. Korobova; O. V. Stanevich; A. A. Lebedeva; E. A. Vorobyov; S. V. Vorobyova; A. N. Kulikov; D. A. Lioznov; M. A. Sharapova; D. E. Pevtcov; et al. (Медицинская иммунология)
COVID-19, an infection caused by the new coronavirus SARS-CoV-2, is associated with a number of pathophysiological mechanisms, mobilizing a wide spectrum of biomolecules, mainly, cytokines.The purpose of this study was to evaluate levels of multiple cytokines in blood plasma from the patients with COVID-19 during acute phase of the disease, and upon complete recovery. Samples of peripheral blood plasma of 56 patients with COVID-19, 69 convalescents and 10 healthy individuals were examined. Concentrations of 46 molecules, such as IL-1α, IL-1β, IL-2, IL-3, IL-4, IL-5, IL-6, IL-7, IL-9, IL-12 (p40), IL-12 (p70), IL-13, IL-15, IL-17A/CTLA8, IL-17-E/IL-25, IL-17F, IL-18, IL-22, IL-27, IFNα2, IFNγ, TNFα, TNFβ/ Lymphotoxin-α (LTA), CCL2/MCP-1, CCL3/MIP-1α, CCL4/MIP-1β, CCL7/MCP-3, CCL11/Eotaxin, CCL22/MDC, CXCL1/GROα, CXCL8/IL-8, CXCL9/MIG, CXCL10/IP-10, CX3CL1/Fractalkine, IL-1ra, IL-10, EGF, FGF-2/FGF-basic, Flt3 Ligand, G-CSF, M-CSF, GM-CSF, PDGF-AA, PDGF-AB/ BB, TGF-α, VEGF-A were measured via xMAP multiplexing technology. Significantly increased levels of 18 cytokines were found in blood plasma from COVID-19 patients during acute phase of the disease (as compared to control group), i.e., IL-6, IL-7, IL-15, IL-27, TNFα, TNFβ/Lymphotoxin-α (LTA), CCL2/MCP-1, CCL7/MCP-3, CXCL1/GROα, CXCL8/IL-8, CXCL10/IP-10, CXCL9/MIG, IL-1rа, IL-10, M-CSF, GM-CSF, VEGF-A. We found a significant decrease of nearly all the mentioned cytokines in recovered patients, in comparison with those who had moderate, severe/extremely severe disease. Moreover, we revealed a significantly decreased level of 8 cytokines in plasma from convalescents, as compared with control group, i.e., IL-1α, IL-2, IL-9, IL-12 p40, IL-18, CCL22/MDC, Flt3 Ligand, TGF-α. Immune response caused by SARS-CoV-2 infection involves multiple cytokines, mostly, with pro-inflammatory effects. We have shown for the first time that the convalescence phase is characterized by significantly lower levels of cytokines which regulate cellular differentiation and hematopoiesis (in particular, lymphocytes, T-cells and NK-cells). Over acute phase of the disease, the levels of these cytokines did not change. We revealed a significant decrease of most plasma cytokines upon recovery as compared to acute phase. On the contrary, acute phase of the disease is accompanied by significant increase of both pro- and antiinflammatory cytokines in blood plasma.